2009
DOI: 10.1596/978-0-8213-7900-4
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Life and Service Delivery in Eastern Europe and the Former Soviet Union

Abstract: World Bank Working Papers are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally-edited texts. Some sources cited in this paper may be informal documents that are not readily available. The findings, interpretations, and conclusions expressed herein are those of the author(s) and do not necessarily reflect the views of the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Due to low response rates, actual or imputed rents are not included. Previous analysis showed that the consumption aggregates constructed from LiTS I compare well with conventional measures based on national accounts and household surveys (see Zaidi et al, 2009). 4…”
Section: Comparing Subjective and Objective Measures Of Crisis Impact Across Householdsmentioning
confidence: 85%
“…Due to low response rates, actual or imputed rents are not included. Previous analysis showed that the consumption aggregates constructed from LiTS I compare well with conventional measures based on national accounts and household surveys (see Zaidi et al, 2009). 4…”
Section: Comparing Subjective and Objective Measures Of Crisis Impact Across Householdsmentioning
confidence: 85%
“…collective mobility (Gugushvili, in press). But when the answers on subjective intergenerational mobility are contrasted with individuals' perceptions on how well they have done in life when compared with their high school classmates and colleagues (measuring collective mobility), subjective intergenerational mobility still maintains unique variations and therefore can serve as an alternative indicator of objective intergenerational mobility (Zaidi et al, 2009). Figure 1 shows the distribution of occupational and perceived intergenerational mobility in the pooled sample of post-socialist societies.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Many studies hypothesize the relationship between place of residence and life satisfaction in older ages. In the work of Salman Zaidi and co-authors (Zaidi et al 2009), the authors concluded that residents of metropolitan areas are less happy than residents of small towns.…”
Section: Demographic Characteristics: Age Sex Place Of Residencementioning
confidence: 99%